Answer:
5(2a − 3) = (2a − 3) ⋅ 5
Step-by-step explanation:
Commutative Property of Multiplication is switching the order of the numbers around, and that answer demonstrates just that.
let the two numbers be x and y
From the first sentence,
xy=24
x+y=10
Then make y in equation 2 the subject of the formular and substitute in equation 1
x+y=10
y=10-x
substituting in equation 2
x(10-x)=24
open the bracket
10x-x^2=24
=-x^2+10x=24
Transfer the constant to the left hand side
=-x^2+10x-24=0
Then factorise completely
Look at the photo above
Answer: 2/125
Step-by-step explanation: No esto 100% seguro pero hice esto:
2/5 % 4 = 2/125
Square inside the first parentheses,, then square outside both.
Answer: 2.25
Answer:
-9
Step-by-step explanation:
-3|16-20|+9/3
-3|-4|+3
-3*4+3
-12+3
-9